Ophiocordyceps taiwanensis sp. nov. (Ophiocordycipitaceae, Hypocreales) on Odontotermes formosanus (Termitidae, Blattodea) - Samarakoon, Milan C.; Hsu, Kun-Chin; Chiu, Chun I; Chen, Chi-Yu; Li, Hou-Feng; Haituk, Sukanya (Phytotaxa, 2024)
Ophiocordyceps species are found worldwide, with their greatest diversity occurring in tropical and subtropical regions, particularly in Southeast Asia. In June 2020, during a study conducted in Taiwan, stromata associated with dead termite alates (or winged termites) (Odontotermes formosanus) were collected and characterized. This study identified a unique sexual morph, Ophiocordyceps taiwanensis sp. nov., distinguished by its asci and ascospore morphology compared to the majority of Ophiocordyceps species. Our new collection exhibits similarities to O. bispora (≡ Cordycepioideus bisporus), particularly in having asci with two ascospores. However, it differs in the shape of its perithecia, which are subglobose to ovoid, and in possessing smaller, aseptate ascospores. Phylogenetic analysis using various gene combinations in both preliminary and final LSU-ITS-SSU-TEF1-RPB2 sequence alignments revealed that our new isolates form a clade closely related to O. bispora KVL 606, supported by 88% MP/100% ML/1.00 PP BI statistical support. Based on its distinct morphology and phylogenetic placement, we propose O. taiwanensis as a new species, representing the first recorded instance of an Ophiocordyceps species associated with termites in Taiwan.